Structural characterization, biological evaluation and DNA interaction of some potential drugs based on bifunctional aldehyde functionality - Naz, Mehwish; Akhter, Zareen; Zaka, Ayesha; Mirza, Bushra; McKee, Vickie; Ullah, Ehsan; Bolte, Michael (European Journal of Chemistry, 2017)
Recent work aimed at evaluating the possibility of enhancing biological activities by synthetically modifying bifunctional aldehyde structures. In this article, two series of bifunctional aldehydes were synthesized, structurally characterized (M-1A, M-1C and M-2A) using single crystal X-ray diffraction analysis. Several pharmacological properties like cytotoxic, antifungal, antibacterial, antioxidant and antitumor activities were also evaluated. In addition, bifunctional aldehyde-DNA interaction assay was examined by UV-Vis spectroscopy which revealed the DNA damaging behaviour of these aldehydes. The results of UV-Vis spectroscopy were supported by DNA damaging assay. The overall results reveal that bifunctional aldehyde moiety could be used as potential drug candidates.